THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF THE ANTI-CORRUPTION POLICIES OF STATES IN THE INTERNATIONAL BANKING AND FINANCIAL SPHERE - Nilufar Doniyorkhodjaevna Doniyorkhodjaeva (Web of Journals Publishing, 2024)
In this article, exploring the theoretical and methodological foundations of the formation of anti-corruption policies of states in the international banking and financial sphere, the author notes that international legal anti-corruption policy in the banking and financial sector is the activity of states, international organizations, regional associations, and other subjects of international relations that have a special status for creating, ensuring political and legal conditions for combating and minimizing corruption in the banking and financial sector. This policy has both public law aspects (the sphere of relations arising between states, international financial and other public organizations, and private law components (relations between transnational corporations and other subjects of international commercial relations related to banking and financial transactions).
Keywords: theory, methodology, corruption, states, policy, banking, finance.